An electrochemiluminescence sensor based on a sulfur-terminal CdS2L complex. Issue 16 (21st August 2015) - Zhang, Chunyan; Wang, Lei; Zhang, Shengyi; Mao, Changjie; Song, Jiming; Niu, Helin; Jin, Baokang; Tian, Yupeng
<x xml:space="preserve">Abstract</x> A sulfur-terminal CdS2L complex was synthesized by a solvothermal reaction, and its electrochemiluminescence (ECL) properties were studied. A solid-state ECL sensor was fabricated with the CdS2L complex, with a linear range from 0.002 mM to 4 mM and a detection limit of 0.67 nM for GSH.